Transcutaneous Interference Spinal Cord Stimulation: Leadfield-Based Pareto Optimization of Electrode Montages for Improved Focality - Medina-Daza, L (Springer Verlag, 2025)
This study investigates the feasibility of transcutaneous interferential spinal cord stimulation (tISCS), a novel non-invasive neuromodulation method, using temporal interference to enhance focality and comfort in spinal cord stimulation. The central research question is whether tISCS can achieve targeted activation of spinal cord circuits while reducing unwanted stimulation of skin and muscle tissues, which are common limitations of conventional transcutaneous spinal cord stimulation (tSCS). A finite element model of the lower thorax was developed to simulate electric field distributions for various skin electrode montages. To address the computational bottleneck associated with high-resolution modeling and montage optimization, we implemented a leadfield-based Pareto optimization strategy to identify the electrode configuration that maximizes the electric field in the spinal cord and minimizes it in off-target tissues. tISCS montages were compared with tSCS montages in terms of focality and stimulation efficiency. Optimized tISCS configurations significantly reduced electric field intensity in the skin by over 20-fold compared to tSCS. The ratio of spinal cord to skin electric fields increased by at least tenfold, indicating enhanced focality. The injection current efficiency in tISCS can be leveraged to increase spinal cord electric fields by at least fivefold while keeping skin exposure below the levels observed with tSCS. tISCS enables deeper and more selective spinal cord stimulation compared to tSCS, with substantially reduced off-target effects. In conclusion, this is the first computational demonstration of tISCS feasibility, and leadfield-guided Pareto optimization enables efficient montage selection, providing a foundation for future experimental applications. © The Author(s) 2025.